Combining fundamental studies with advanced characterization for analyzing nitric oxide polymer systems - Joslin, Jessica Marie, author; Reynolds, Melissa M., advisor; Ladanyi, Branka M., committee member; Krummel, Amber T., committee member; Ackerson, Christopher J., committee member; Williams, John D., committee member (Colorado State University. Libraries, 2014)
Nitric oxide (NO) releasing materials have been investigated over the past couple of decades as potential biomaterials. A multitude of NO releasing platforms have been reported with different NO release properties indicating use in various bioapplications. Despite the positive implications associated with these materials, the field is currently limited by a couple of major issues. First, the reservoirs of NO stored in current systems do not allow the prolonged and controllable release necessary for long-term usage. Additionally, the field has experienced a lack of complete characterization of both the NO loading and release processes associated with these systems. To develop NO releasing platforms with enhanced NO reservoirs and controllable NO release profiles, fundamental studies are required to probe the physical processes that occur in these polymers. To enhance NO reservoirs in polymer systems, it is critical to probe the efficiency of the NO loading process. Systematic studies are presented where the efficiency and nature of S-nitrosothiol NO donor formation is investigated in a polymer environment. The nitrosating agent and polymer presence have a significant impact on the kinetics of S-nitrosation. Also, due to the versatile nature of nitrosation, NO byproducts that form competitively with S-nitrosothiols are characterized. By tuning the polymer functional groups, competitive nitrosation products can be eliminated and NO recoveries enhanced. Another critical obstacle towards understanding NO materials involves probing NO donor behavior in conjunction with NO release. For model polymers containing covalently linked S-nitrosothiol moieties, spectroscopy is coupled to direct NO detection to fully characterize the NO loading and release stages. Decomposition of the S-nitrosothiol moiety is directly correlated to NO release. S-nitrosothiol blended films are also investigated to determine the spatial distribution of NO release, which is critical to ensure a localized NO effect at the material surface. Finally, NO releasing polymer substrates are exposed to water plasma processing conditions. Surface wettability is significantly enhanced, while the NO release kinetics are maintained, suggesting that these materials can withstand processing towards tunable surface properties. Overall, fundamental and systematic studies of model NO releasing materials are presented that have not been formerly considered. Only by characterizing these materials completely can this class of biomaterial be better understood towards the ability to control the therapeutic and surface properties.
Keywords: characterization; nitric oxide; polymer; S-nitrosothiol